An Empirical Study on the Impact of Individual and Organizational Supply Chain Orientation on Supply Chain Management - Taehee Lee (Asian Journal of Shipping and Logistics, 2016)
This study empirically identifies individual supply chain orientation (SCO) components as antecedents of organizational SCO and analyzes the causal relationships between organizational SCO and supply chain management (SCM). A survey was conducted with Korean firms and the partial least squares method was used to test the proposed hypotheses. The results show that individual SCO has a significant influence on organizational SCO. Organizational SCO has a significant influence on strategic SCM, whereas only information technology for SCO affects operational SCM. Strategic SCM has a significant influence on operational SCM. This study extends our understanding of the social and behavioral elements of SCM by classifying SCO into individual and organizational SCO and identifying the causal relationships between them.